Non-invasive diagnosis of cardiac rejection using small non-coding RNAs. (3rd October 2022) - Gimenez-Escamilla, I; Perez-Carrillo, L; Sanchez-Lazaro, I; Martinez-Dolz, L; Portoles, M; Tarazon, E; Rosello-Lleti, E
Abstract: Background: Endomyocardial biopsy is the standard technique for rejection surveillance in heart transplantation recipients and is an invasive method with important limitations and clearly associated with both a risk of procedural complications and serious long-term sequelae when performed repeatedly. All of these considerations highlight the need to identify non-invasive alternative methods capable of discriminating between the different grades of rejection and reducing the need for endomyocardial biopsy. Purpose: We conducted a non-targeted transcriptomic study focused on identifying serum small non-coding RNAs, mainly aimed on the less studied types, to evaluate their diagnostic accuracy for detecting rejection episodes. Methods: We included consecutive serum samples from transplant recipients undergoing routine endomyocardial biopsies. Non-coding RNA sequencing analysis (Illumina HiSeq 2500) was performed on 40 samples, 28 diagnosed with RCA (RCA Grade 1R, n=16; and RCA Grade ≥2R, n=12) and 12 samples without cardiac rejection. Results: 636 non-coding RNAs were detected among the scaRNAs, snoRNAs, snRNAs and miscRNAs biotypes. But, neither piRNA nor siRNA biotypes were detected. Of all of them, 41 were altered in patients with rejection Grade ≥2R, finding no alteration in the scaRNAs biotype. Three molecules of miscRNA biotype showed the best results with excellent diagnostic capacity in moderate/severe rejection: RN7SL840P (AUC=0.938, p<0.01), Y_RNA [ENSG00000223302] (AUC=0.931, p<0.0001) and Y_RNA [ENSG00000202273] (AUC=0.903, p<0.001). In addition, RN7SKP5 showed a good capacity for the diagnosis of Grade ≥2R (AUC=0.806, p<0.05) and preserving the accuracy at Grade 1R (AUC=0.781, p<0.05). Conclusions: The 6.5% of the small non-coding RNAs detected have differential expression in patients with acute cellular rejection. The non-detection of the piRNAs and siRNAs biotypes stands out, as well as the absence of alteration in the scaRNAs biotype. We propose serum miscRNA levels as potential biomarkers of cardiac rejection. We highlight the role of RN7SL840P due to its excellent diagnostic capacity for RCA, and RN7SKP5 since it also allows the detection of mild rejection. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Carlos III European Regional Development Fund (ERDF)